Exploring Soil Bacterial Diversity in Relation to Edaphic Physicochemical Properties of High-altitude Wetlands from Argentine Puna - Mlewski, Estela Cecilia; Saona, Luis A.; Boidi, Flavia Jaquelina; Chiappero, María Fernanda; Vaieretti, María Victoria; Soria, Mariana; Farías, María Eugenia; Izquierdo, Andrea E. (Springer, 2024)
High Andean wetlands, particularly those known as vegas or bofedales, are essential conservation ecosystems due to their significant contribution to ecosystem services. The soil microbial communities in these ecosystems play a crucial role in fundamental processes such as decomposition and nutrient cycling, sustaining life in the region. However, at present, these microbial communities are poorly understood. In order to contribute to this knowledge, we aimed to characterize and compare the microbial communities from soils of seven Argentine Puna vegas and to analyze their association with soil physicochemical characteristics. Proteobacteria (Gamma and Alphaproteobacteria) was the dominant phylum across all vegas, followed in abundance by Actinobacteriota, Desulfobacterota, and Chloroflexi. Furthermore, the abundance of specific bacterial families and genera varied significantly between the vegas; some of them can be associated with plant growth-promoting bacteria such as Rhodomicrobium in La Quebradita and Quebrada del Diablo, Bacillus in Antofalla and Las Quinuas. Laguna Negra showed no shared ASVs with abundance in genera such as Sphingomonas and Pseudonocardia. The studied vegas also differed in their soil physicochemical properties; however, associations between the composition of microbial communities with the edaphic parameters measured were not found. These results suggest that other environmental factors (e.g., geographic, climatic, and plant communities’ characteristics) could determine soil microbial diversity patterns. Further investigations are needed to be focused on understanding the composition and function of microorganisms in the soil associated with specific vegetation types in these high-altitude wetlands, which will provide valuable insights into the ecological dynamics of these ecosystems for conservation strategies.